EFEKTIVITAS TEKNIK MIND MAP DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MENULIS KARANGAN ILMIAH SISWA - yunisa oktavia; Dairi Sapta Rindu Simanjuntak (Jurnal Pendidikan Bahasa Indonesia, 2022)
Learning to write scientific essays is an important part of the Indonesian language curriculum because students must be active writers who pay attention to the rules and realm of writing. Students' difficulties in determining topics, expressing ideas in scientific writings, arranging effective sentences, and writing Indonesian spelling errors motivated the research. Furthermore, writing scientific essays is not an easy task for students because it necessitates a great deal of practice in order for students to become accustomed to writing scientific essays in accordance with the provisions. The goal of this study was to describe the efficacy of this experimental type of research, which was conducted on class XII students at SMK Negeri 5 Batam using test research instruments and questionnaires. According to the findings of the data analysis and discussion, there is an effective mind map technique on students' scientific essay writing skills because t hit = 3.61 while t tabel = 1.661 means t hit> t tabel with dk = 76. Second, the result score of scientific essay writing skills of students with high learning motivation who are taught using mind mapping techniques is higher than the result score of students with high learning motivation who are taught using conventional methods because t hit = 1,865, whereas t _table = 1.729 at the significant level with = 0.05 and dk = 37. Third, students with low learning motivation who are taught using mind mapping techniques have higher scientific essay writing skills than students who are taught using conventional methods because t hit= 3.563, while t tabel = 1.721 at the significant level with = 0.05 and dk = 31. Fourth, F 3 F table (0.30 1.53) is not t for interaction = 0.05. There is an interaction between the mind map technique and students' motivation to learn Indonesian language learning outcomes for SMK Negeri 5 Batam class XII students.